Mapping the Relevance of Library Science Curriculum and Graduates Competencies: A Survey - Irvan Muliyadi (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2022)
Higher education should continuously ensure the link and match between curriculum and the work competency of the graduates. This study uses a survey method to foster the level of relevance of the LIS curriculum with the work competency of the LIS graduates. Seventy-six graduates participated in this survey to map the level of relevance of the 30 major courses of the LIS curriculum with their work competency. The result of this study shows that Computer Applications and Internet (92.3%), and cataloging for a monograph (91.5%) have a very high level of relevance with the work competency of the graduate. It indicates that the teaching materials on information organization and ICT use in the library should comprehensively and deeply be presented in LIS courses to strengthen such competencies. Similarly, Library Internship (91.3%), a course required to enhance any work competency of a LIS graduate, is very relevant to the work competency of the graduate. This means that the majority of LIS courses should involve a significant amount of the practical component. Bibliometric and Secondary Literature only show 47.8% and 50.5% of relevance for the two themes, respectively. The teaching materials for Bibliometric and Secondary Literature should not be described in as much length as other courses within the LIS curriculum because of the neutral degree of relevance of these two courses.